HUBUNGAN PELAKSANAAN TINDAKAN KEPERAWATAN BERDASARKAN KEBUTUHAN DASAR MANUSIA VIRGINIA HANDERSON DENGAN KEPUASAN PASIEN DI RS BHAYANGKARA WAHYU TUTUKO BOJONEGORO - Kurniati, Mei Fitria; Abidin, Ahmad Zainal Abidin (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
The nurse is obligated to examine the basic human needs for determining the action plan and implementation to be delivered tro the patient. Patient satisfaction is one indicator of the quality of service we provide and patient satisfaction is a capital to get more patients and to get patients loyalty.The purpose of this study is to know the relationship of implementation of nursing actions based on basic human needs from Virginia Handerson with satisfaction of patient at Bhayangkara Wahyu tutuko Bojonegoro Hospital This research desaign using Cross Sectional. The sampling methode used is Purposive Sampling. A sampling of 23 nurses and 30 patients met the inclution criteria. The variables studied are the independent variables of nursing action and the dependent variable is patient satisfaction. Data were collected using questionnaire and analyzed by using Spearman Rho test with significance level 0,05. The result showed that all nurses performed a good nursing action that is as much  as 23 respondents (100 %).Patient satisfaction data found that most of respondents stated very satisfied that as many as 29 respondents (96.7%) and 1 respondent (3.3%) expressed satisfaction. The result of Spearman Rho test showed sig. ρ = 0,000 means ρ <0.05 so that  is accepted so that there is a relationship of implementation of nursing actions based on basic human needs from Virginia Handerson with satisfaction of patient at Bhayangkara Wahyu tutuko Bojonegoro Hospital. Nurses should be more active to improve the quality of the implementation of nursing actions by meeting basic human needs as a responsibility in providing professional services to improve patient satisfaction as a service user